ANALISIS DAMPAK SOSIALIASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PENGETAHUAN PERPAJAKAN SEBAGAI VARIABEL INTERVENING PADA PEGAWAI RUMAH SAKIT ESTOMIHI MEDAN - Hendrik E. S. Samosir; Hanna M. Damanik; Martin Luter Purba (Universitas Methodist Indonesia, 2021)
This study aims to see the effect of tax socialization obtained by employees on employee compliance at Estomihi Hospital Medan by using tax knowledge as an intervening variable. This research is field research, and the research design is explanatory using 60 respondents as the research sample. The results of this study indicate that the better the socialization provided to taxpayers will have an impact on increasing the knowledge of taxpayers; The better knowledge of taxation will have an impact on increasing taxpayer compliance in carrying out their obligations; Tax socialization does not directly impact on taxpayer compliance through taxation socialization will provide knowledge to taxpayers so that taxpayers who have good knowledge will have compliance in carrying out their obligations as good taxpayers.